Relevansi Pemikiran Religius-Rasional Jalaluddin Rakhmat Dalam Pengembangan Pendidikan Islam Kontemporer - Eni Hidayati; Maragustam; Fery Andryanto (TAUJIH: Jurnal Pendidikan Islam, 2025)
Contemporary Islamic education faces a crisis of integration between faith and rationality due to the rapid flow of globalization and modernity. This condition raises academic concerns because the education system often fails to shape a Muslim personality that is both rational, spiritual, and moral. This study aims to analyze the rational religious thought of Jalaluddin Rakhmat and its relevance to the development of contemporary Islamic education. The method used is qualitative research with a library research approach, by examining Jalaluddin Rakhmat's works, such as Psychology of Communication, Psychology of Religion, Islam Aktual, and secondary literature from scientific journals. The results show that Rakhmat's thinking rejects the dichotomy between revelation and reason, and presents an integrative approach that combines religious values ​​with modern rationality. He adopted the concept of quantum learning to enrich Islamic education, emphasizing the importance of spiritual intelligence as the foundation of student development, and making religious ethics sourced from the Qur'an, Sunnah, and ushul fiqh as the orientation of education. The relevance of this thinking is evident in efforts to develop a contextual curriculum, spirituality-based learning strategies, and rational and inclusive character education. The implications of this research show that Jalaluddin Rakhmat's religious-rational model can be used as a reference in building a moderate, humanistic, and transformative Islamic education system, so that it is able to answer the challenges of a multicultural society in the modern era.